2012
DOI: 10.1007/s12013-012-9355-0
|View full text |Cite
|
Sign up to set email alerts
|

Better Prognosis in Newborns with Trisomy 13 Who Received Intensive Treatments: A Retrospective Study of 16 Patients

Abstract: Intensive treatment for newborns with trisomy 13 is controversial because of their lethal prognosis. We report the better life prognosis of patients with trisomy 13 who received intensive treatment. At our hospital, we provided an intensive management to such patients including resuscitation and surgical procedures as required. Herein, we present the results of a retrospective study (1989–2010) of 16 trisomy 13 cases who received an intensive treatment. None was diagnosed to have trisomy 13 before birth; 9 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…Importantly, in Hsu and Hou's sample, there was only one occurrence of holoprosencephaly and none in the TRIS project sample. Tsukada et al [2012] identified this condition in four cases (n ¼ 16) with longest survival of 50 days. The absence of this brain anomaly may be an additional factor in long-term survival.…”
Section: Confirm and Disconfirm Previous Findingsmentioning
confidence: 98%
See 3 more Smart Citations
“…Importantly, in Hsu and Hou's sample, there was only one occurrence of holoprosencephaly and none in the TRIS project sample. Tsukada et al [2012] identified this condition in four cases (n ¼ 16) with longest survival of 50 days. The absence of this brain anomaly may be an additional factor in long-term survival.…”
Section: Confirm and Disconfirm Previous Findingsmentioning
confidence: 98%
“…ASD was the most prevalent in the TRIS project sample (66% at birth and 55% at survey completion). Tsukada et al [2012] report on 16 patients. Approximately half of the sample was diagnosed with ASD, PDA, and/or VSD.…”
Section: Confirm and Disconfirm Previous Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…The most common aneuploidies in South Africa caused by autosomal chromosomal abnormalities include Down syndrome (Trisomy 21), Edward syndrome (Trisomy 18) and Patau syndrome (Trisomy 13). Globally the incidence for Down syndrome is about 1 in 650 to 1000 live births [2], Edward syndrome is 1 in 6000 live birth [3], and Patau is between 1 in 5000 to 29000 live birth [4]. Currently the prevalence rate is 1 out of 500 live birth for Down syndrome in South Africa with 1886 new cases diagnosed every year [5] and for Edward syndrome the prevalence is 1 in 4000 live birth and Patau is 1 in 8889 live birth [6,7].…”
mentioning
confidence: 99%